Strategies of Boundary Setting in Women Healing from Familial Emotional Abuse - Lee, Angel; Yildiz, Emre; Chaudhary, Aman Ullah (Psychology of Woman Journal, 2024)
Objective: This study aimed to explore the boundary-setting strategies employed by women healing from familial emotional abuse.Methods and Materials: Using a qualitative research design, this study recruited 31 women from various regions of Turkey who self-identified as survivors of familial emotional abuse. Participants were selected through purposive sampling, and data were collected through in-depth, semi-structured interviews. Interviews focused on participants’ experiences of emotional abuse and the specific strategies they employed to assert emotional and relational boundaries during their healing process. Data collection continued until theoretical saturation was reached. All interviews were transcribed verbatim and analyzed thematically using NVivo software, following an inductive coding approach. Ethical approval was obtained, and informed consent was provided by all participants.Findings: Thematic analysis revealed three overarching categories of boundary-setting strategies: Reclaiming Autonomy, Restructuring Familial Relationships, and Emotional Self-Preservation. Each category included multiple subcategories such as asserting personal space, decision-making independence, limiting contact, managing conversations, detaching from guilt, and reframing abuse narratives. Participants described boundary setting as a deeply emotional, complex process involving both external actions and internal cognitive shifts. Strategies were often enacted amidst cultural norms discouraging familial confrontation and individual autonomy. Despite these challenges, participants reported a gradual strengthening of self-worth, emotional regulation, and relational clarity as a result of these practices.Conclusion: The findings underscore the need for trauma-informed, culturally sensitive clinical practices that validate and support women’s efforts to assert boundaries as a form of healing and empowerment.